A systematic review of diagnostic methods to differentiate acute lung injury/acute respiratory distress syndrome from cardiogenic pulmonary edema - Kosaku Komiya; Tomohiro Akaba; Yuji Kozaki; Jun-ichi Kadota; Bruce K. Rubin (Critical Care, 2017)
Abstract Background Discriminating acute lung injury (ALI) or acute respiratory distress syndrome (ARDS) from cardiogenic pulmonary edema (CPE) is often challenging. This systematic review examines studies using biomarkers or images to distinguish ALI/ARDS from CPE. Methods Three investigators independently identified studies designed to distinguish ALI/ARDS from CPE in adults. Studies were identified from PubMed, and the Cochrane Central Register of Controlled Trials database until July 3, 2017. Results Of 475 titles and abstracts screened, 38 full texts were selected for review, and we finally included 24 studies in this systematic review: 21 prospective observational studies, two retrospective observational studies, and one retrospective combined with prospective study. These studies compared various biomarkers to differentiate subjects with ALI/ARDS and in those with CPE, and 13 calculated the area under the receiver operator characteristic curve (AUC). The most commonly studied biomarker (four studies) was brain natriuretic peptide (BNP) and the discriminatory ability ranged from AUC 0.67–0.87 but the timing of measurement varied. Other potential biomarkers or tools have been reported, but only as single studies. Conclusions There were no identified biomarkers or tools with high-quality evidence for differentiating ALI/ARDS from CPE. Combining clinical criteria with validated biomarkers may improve the predictive accuracy.